Integrating the costs of a manufacturing IT/IS infrastructure into the investment decision-making process - Irani, Z. (Technovation)
Due to the increasing level of organisational investment in Information Technology (IT) and Information Systems (IS), significant amounts of capital need justifying. However, many companies are reporting their inability to justify their investment in IT/IS because of the nature of costs and benefits associated with its implementation The reason for this is that many organisational budgeting processes rely on financially oriented appraisal techniques as an integral part of the decision-making process. These accountancy frameworks are often used to assess the 'bottom-line' financial impact of an investment by setting tangible project costs against those quantifiable benefits and savings predicted to be achievable. However, traditional appraisal techniques are considered to be no longer appropriate in justifying investments in IT/IS because of the nature of intangible benefits, together with the complexity of direct and indirect cost implications. Hence, the predictive value of using many traditional investment appraisal techniques is increasingly being questioned. The authors of this paper have identified and then classified a variety of appraisal techniques that are used during the justification of capital investments in IT/IS. The taxonomy developed provides a critique of characteristics for both traditional and non-traditional appraisal techniques. The authors then identify a range of cost implications associated with the adoption of IT/IS, with a particular focus on manufacturing applications. These cost implications are then developed into a taxonomy of direct and indirect costs, which clearly need consideration during the investment decision-making process.